Cost-effectiveness of letermovir as cytomegalovirus prophylaxis in adult recipients of allogeneic hematopoietic stem cell transplantation in Hong Kong. (1st December 2020) - Chan, Thomas Sau-Yan; Cheng, Sally Shuk-Yee; Chen, Wei-Ting; Hsu, Danny Chung; Chau, Rene Wing-Yan; Kang, Suk Hyun; Alsumali, Adnan; Kwong, Yok-Lam
Abstract: Background: The cost-effectiveness of letermovir as cytomegalovirus (CMV) prophylaxis in adult seropositive patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT), compared with the conventional strategy of preemptive treatment, has not been evaluated in Asia. Methods: A decision analytical model, simulating the clinical progression of CMV infection on a lifetime horizon, was developed to compare prophylactic strategy with letermovir with preemptive therapy alone as anti-CMV strategies. Prophylaxis comprised administering letermovir for 14 weeks, with clinical outcomes measured at 24 weeks, followed by preemptive therapy if CMV infection occurred. This approach was modeled on outcomes of the letermovir phase 3 clinical study. The model enumerated the cost of letermovir prophylaxis, quality-adjusted life years (QALYs), and incremental cost per QALYs gained with prophylaxis. The opposite arm involved regular monitoring and preemptive therapy for CMV reactivation. Real-world costs from the adult HSCT center at Queen Mary Hospital, Hong Kong, were adopted for analysis. Costs and clinical benefits, expressed as QALYs, were discounted at 3% per year. Results: Letermovir prophylaxis compared with preemptive therapy only would lead to an increase of life-year and QALYs at increased costs. Incremental cost-effectiveness analysis showed that letermovir prophylaxis had an associated cost of HKD 193, 580 for each life-year gained, and HKD 234, 675 for each QALY gained. Probabilistic sensitivity analysis showed that the majority of incremental cost-effectiveness ratio fell below the cost-effectiveness threshold of HKD 382, 046 (one gross domestic product per capita) per QALY gained. Conclusions: Letermovir prophylaxis would be cost-effective for preventing CMV infection in adult seropositive allogeneic HSCT recipients in Hong Kong.